Factors driving historic intercontinental invasions of European pine bark beetles - Vilardo, Gimena (2022)
Largely assisted by global trade, alien insect species are being introduced into new territories at unprecedented rates. Among forest insects, pine bark beetles (Coleoptera: Curculionidae, Scolytinae) are a large and diverse group commonly recognized as successful invaders and important tree mortality agents in pine forests and commercial plantations. In this study, we collected information on the native and invaded distribution of 51 European bark beetles developing in Pinus species. We analyzed their invasion history in the Southern Hemisphere and the Americas and explored several factors that can help explain their invasion success: (1) propagule pressure: interception frequency in the non-native range(2) invasibility: potential establishment area based on climatic matching and host availability and (3) invasiveness: biological traits of the bark beetles (i.e., feeding habit, host range, body size, mating system, colonization behavior). We found that most (87%) of the introductions of the species to new regions occurred in the period 1960–2013, and that variables related with the three main factors were relevant in explaining invasion success. Propagule pressure was the factor that best explained bark beetle invasion probability, followed by invasibility of the novel area. In turn, biological attributes like mating system, body size and host range were also relevant, but showed a lower relative importance. Our study contributes to understand the main factors that explain forest insect invasion success. This information is critical for predicting future invasions to new regions and optimizing early-detection and biosecurity policies.